2016
DOI: 10.1038/ajg.2016.436
|View full text |Cite|
|
Sign up to set email alerts
|

Association of Hepatitis B Core-Related Antigen With Hepatitis B Virus Reactivation in Occult Viral Carriers Undergoing High-Risk Immunosuppressive Therapy

Abstract: Serum HBcrAg positivity is a significant risk factor of HBV reactivation in HBsAg-negative, anti-HBc-positive patients undergoing high-risk immunosuppressive therapy and can potentially have a role in identifying patients who will best benefit from prophylactic nucleoside analogue treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(44 citation statements)
references
References 34 publications
0
44
0
Order By: Relevance
“…In this regard, a recent study has shown that positivity to HBV core‐related antigen (HBcrAg) is a significant risk factor for HBV reactivation in anti‐HBc‐positive/HBsAg‐negative patients. This biomarker can potentially have a role in identifying patients who will benefit from anti‐HBV treatment …”
Section: Discussionmentioning
confidence: 99%
“…In this regard, a recent study has shown that positivity to HBV core‐related antigen (HBcrAg) is a significant risk factor for HBV reactivation in anti‐HBc‐positive/HBsAg‐negative patients. This biomarker can potentially have a role in identifying patients who will benefit from anti‐HBV treatment …”
Section: Discussionmentioning
confidence: 99%
“…This aberrant protein was also named HBcrAg. In the literature, the term “HBcrAg” has been used to describe a combination of HBc and HBe [13,86,87,88]; the supposedly aberrant p22cr [47]; and a combination of all three entities, HBc, HBe, and p22cr [89,90,91]. As discussed above, the so-called p22cr probably does not really exist and the current HBcrAg ELISA kit most likely detects a combination of HBcAg (released from virions) and HBeAg.…”
Section: Potential Applications Of Hbv Particles In Clinical Managmentioning
confidence: 99%
“…It was also found to predict liver cancer development and recurrence in HBV-infected patients, and was an even better predictor than serum HBV DNA [92,94]. Serum HBcrAg was also found to associate with reactivation of occult hepatitis B following immunosuppressive therapy [91]. …”
Section: Potential Applications Of Hbv Particles In Clinical Managmentioning
confidence: 99%
“…Serum HBcrAg levels were measured using a CLEIA HBcrAg Assay Kit (Fujirebio, Inc, Tokyo, Japan) according to the manufacturer's instructions on a Lumipulse G1200 Automated Analyzer (Fujirebio, Tokyo, Japan). The HBcrAg value was expressed as log U/mL, and the lower limit of detection was 2 log U/mL …”
Section: Methodsmentioning
confidence: 99%